2020
DOI: 10.1021/acsnano.0c07527
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Planar Blocks into Twisted Skeletons: Boosting Brightness of Fluorophores for Bioimaging beyond 1500 Nanometer

Abstract: The brightness of organic fluorescence materials determines their resolution and sensitivity in fluorescence display and detection. However, strategies to effectively enhance the brightness are still scarce. Conventional planar π-conjugated molecules display excellent photophysical properties as isolated species but suffer from aggregation-caused quenching effect when aggregated owing to the cofacial π–π interactions. In contrast, twisted molecules show high photoluminescence quantum yield (ΦPL) in aggregate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

8
2

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 58 publications
3
101
0
Order By: Relevance
“…To detect the excretion of AIEgens with aliphatic chains in vivo directly, we selected four other typical kinds of NIR-II AIE fluorophores in which the two possess aliphatic chains (2TT-oC610B [13] and TT3-oCB [24] ) but the others (TQ-BPN [14] and BPN-BBTD [11] ) do not. With OTPA-BBT (in this work), we PEGylated all the five kinds of AIEgens via Pluronic F127 (Figure 2E) and intravenously injected them to the mice respectively (10 mg kgBW −1 ).…”
Section: In Vivo Bio-excretion and Bio-distribution Of The Aggregatiomentioning
confidence: 99%
“…To detect the excretion of AIEgens with aliphatic chains in vivo directly, we selected four other typical kinds of NIR-II AIE fluorophores in which the two possess aliphatic chains (2TT-oC610B [13] and TT3-oCB [24] ) but the others (TQ-BPN [14] and BPN-BBTD [11] ) do not. With OTPA-BBT (in this work), we PEGylated all the five kinds of AIEgens via Pluronic F127 (Figure 2E) and intravenously injected them to the mice respectively (10 mg kgBW −1 ).…”
Section: In Vivo Bio-excretion and Bio-distribution Of The Aggregatiomentioning
confidence: 99%
“…To detect the excretion of AIEgens with aliphatic chains in vivo directly, we selected four other typical kinds of NIR-II AIE fluorophores in which the two possess aliphatic chains (2TT-oC26B [13] and TT3-oCB [24] ) but the others (TQ-BPN [14] and BPN-BBTD [11] ) do not. With OTPA-BBT (in this work), we PEGylated all the five kinds of AIEgens via Pluronic F127 (Figure 2E) and intravenously injected them to the mice respectively (10 mg kgBW −1 ).…”
Section: Main Textmentioning
confidence: 99%
“…It is found that the introduce of congested 3,4-ethoxylene dioxythiophene (EDOT) or ortho-alkylated thiophene can increase the torsion angle between D/π-bridge and A as well as distort the conjugated backbone, thus boosting the fluorescence quantum yield (QY) in aggregate state. [43][44][45] By contrast, the bared thiophene or meta-alkylated thiophene can hardly constrain the reciprocal intermolecular interactions even further installing more distorted rotors. 46,47 Notwithstanding those intriguing advancement, much effort on developing novel D/π-bridge to enrich the library of NIR-II AIE theranostic agent deserves to be devoted.…”
Section: Introductionmentioning
confidence: 99%